PEDAGOGICAL RESEARCH AND CONTINUOUS TEACHER TRAINING IN THE SCHOOL ENVIRONMENT: A NECESSARY RELATIONSHIP - Castilho Cardoso, Patrick Pacheco [UNESP]; Araujo, Luciana Aparecida [UNESP]; Mosca Giroto, Claudia Regina [UNESP] (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2021)
This literature review article and the descriptive and interpretive analysis aimed to gather, interpret, and analyze publications that discussed the contributions of pedagogical research to the continuing education of teachers in locu as an investigative attitude and inseparable from the teaching work. Publications developed in the period between 2008 and 2017 were analyzed, considering the impact, in this period, produced in the literature on teacher education, through the idea of subject-agent and enhancement of pedagogical research fostered in both initial and continuing teacher education. The results indicated the important relationship between the research activity of pedagogical practice and continuing education in locu as an essential methodological possibility for teacher education. It is concluded that the continuing education of teachers needs to take place in school time and space and value the pedagogical research carried out in locu, intending to assist the teacher in the construction of their professionalism and theoretical deepening which is promoted from experiences.
Keywords: Education; Continuing teacher education; Pedagogical research; Training in locu